2015
DOI: 10.1149/ma2015-02/11/630
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tropical Atmosphere on Corrosion of Different Metals: Corrosivity Measurements of Singapore

Abstract: Corrosion influences and intrudes many parts of our lives. It can cause dangerous and expensive damages. Singapore obviously faces corrosion consequences though there is no direct evidence or record to justify how aggressive and diverse Singapore atmosphere is in terms of corrosion.  However, now there is some light to shed these doubts as standardised atmospheric exposure tests have been established in Singapore. Atmospheric exposure test sites were setup at three locations of Singapore to represent marine, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…8 ). The samples collected from all the sites showed the presence of the same main components: lepidocrocite (γ-FeOOH) and goethite (α-FeOOH), which is consistent with the findings of previous studies [ 6 , 21 , [29] , [30] , [31] ].
Fig.
…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…8 ). The samples collected from all the sites showed the presence of the same main components: lepidocrocite (γ-FeOOH) and goethite (α-FeOOH), which is consistent with the findings of previous studies [ 6 , 21 , [29] , [30] , [31] ].
Fig.
…”
Section: Resultssupporting
confidence: 91%
“…TOW and sulfate deposition rate have an impact on mass loss at sites with both industrial atmosphere and tropical humidity characteristics. A study conducted in tropical areas [ 21 ] reported high TOW and ᶵ4 categories at three sites. The sulfate concentrations at one of the study sites (St John's Island, 16.9 mg/m 2 .d) are consistent with those observed in this study.…”
Section: Resultsmentioning
confidence: 99%